2002
DOI: 10.1001/archneur.59.4.630
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Dementia and Hypersomnolence With Dream-Enacting Behavior

Abstract: Background: Sleep disorders are associated with several types of degenerative dementias, including Alzheimer and prion diseases. Animal models have demonstrated abolition of rapid eye movement atonia, resulting in dream-enacting complex movements termed oneiric behavior, and patients with fatal familial insomnia may have vivid dreams that intrude on wakefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Evidence supporting the idea of mirror activity in a purely sensory domain has been provided by two recent studies on "empathy for touch" [130,131]. Blakemore et al [131], for example, found common S1 activations with a topographic organization during the personal experience of touching stimuli delivered to the face or the neck and the observation of such stimulations in others.…”
Section: From Mirror Neurons To Empathymentioning
confidence: 88%
See 3 more Smart Citations
“…Evidence supporting the idea of mirror activity in a purely sensory domain has been provided by two recent studies on "empathy for touch" [130,131]. Blakemore et al [131], for example, found common S1 activations with a topographic organization during the personal experience of touching stimuli delivered to the face or the neck and the observation of such stimulations in others.…”
Section: From Mirror Neurons To Empathymentioning
confidence: 88%
“…In keeping with this notion, a number of brain systems with mirror properties have also been recently described in the domain of emotion [126][127][128][129] and sensory processing [50,125,[130][131][132][133][134]. Thus, the MMS may be only one of the systems of our social brain that allow us to have a direct experiential knowledge about others.…”
Section: From Mirror Neurons To Empathymentioning
confidence: 99%
See 2 more Smart Citations
“…A dementia syndrome with hypersomnia, enacted dreams and loss of slow-wave sleep has recently been reported [111].…”
Section: Dementiamentioning
confidence: 99%